Detection of Del Phenotype in RH negative blood by using chloroform elution technique and specific sequence Primer-Polymerase Chain Reaction (SSP-PCR) / Nor Arina Che Mohd Noor - Che Mohd Noor, Nor Arina (2015)
DEL phenotype is known as the weakest D antigen in the Rh blood group system. Serologically, DEL phenotype commonly mistyped as true Rh negative. An anti-D immunization may occurred in Rh negative recipient who received blood from the DEL phenotype donor. The goals of the present study were to detect DEL phenotype in Rh negative blood by using chloroform elution technique and specific sequence primer-polymerase chain reaction (SSP-PCR). A total of 43 Rh negative blood donor's samples from National Blood Centre were examined for the Rh phenotyping and the presence of DEL phenotype by using chloroform elution technique and SSPPCR. The Rh negative phenotypes consisted of 79.07% dce, 13.95% dCce, 4.65% dcEe and 2.33% dCe. Chloroform elution technique failed to detect DEL phenotype, but only 2.33% (1/43) Rh negative blood donor's sample was being detected as DEL phenotype by using SSP-PCR. In conclusion, based on these findings, chloroform elution technique might not be an effective method in detection of DEL phenotype. Sensitivity and specificity of molecular typing method can overcome the limitation of serological method in the clinical laboratory. Hence, it is highly recommended to use SSP-PCR in detection of DEL phenotype in Rh negative blood, thus preventing the anti-D immunization.